CHROs: Enablers of Value Creating Boards. Issue 4 (October 2019) - Srinivasan, Vasanthi
Abstract: This article argues that chief human resource officers (CHROs) as directors on the board are strategically best placed to lead conversations pertaining to board processes due to their extensive expertise in talent management. Board composition and managing board processes and dynamics are important aspects of board effectiveness. Using the behavioural perspective to corporate governance, the article holds that the key differentiator in value creating boards are the members, the roles they play and the dynamics that allows them to create value for the firm. CHROs can play a decisive role in the board skill evaluation and incorporation of new and diverse members into boards.